(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Fibroids, the commonest benign pelvic tumor, have a common association with subfertility and increasing maternal age. Placenta praevia and fibroid (if submucous) has an association with placenta accreta. Here we report the case of an elderly primigravida with history of prolong subfertility, admitted with 37 weeks pregnancy with multiple fibroids and central placenta praevia with focal increta. Even with all these complicating factors, with the advent of better uterotonic drugs, conservative management could be considered successfully now-a-days. DOI: http://dx.doi.org/10.3329/jbcps.v32i1.21038 J Bangladesh Coll Phys Surg 2014; 32: 41-44